Emotional Burnout Syndrome as a Central Nervous System Condition Indicator in University Students - Rochev, V alerii (International Journal of Psychosocial Rehabilitation, 2026)
Background: Purpose of the study is the evaluation of the relationship between EBS levels and the state of the university student's CNS condition using V. Boiko’s methodologyMethods: During our examination, V. Boiko's informative, economical and simple express methodology for emotional burnout syndrome assessment was used. Central nervous system condition, psychological and physical health of 75 students of Perm State Agro-Technological University was investigated.Results: The fully formed tension phase was determined in 26 students (34.4%), the resistance phase in 43 (57.1%), the exhaustion phase- in 31 students (41.3%). The relationship between the levels of the burnout syndrome phases and the number of students’ complaints about central nervous system condition has been proved: the smallest number of complaints are presented by probationers with unformed burnout phases, and vice versa, in individuals with forming stages of phases and fully formed phases, the number of complaints growing up.Conclusion: The results of our research indicate an important role of emotional burnout syndrome in mechanisms of various diseases development. Given methodology allows us to provide students health status assessment, conduct the person selection for specialist’s examination: by a psychologist, psychiatrist or therapist. Comprehensive psychological, medical and pedagogical rehabilitation aimed at the central nervous system condition and mental well-being improving university students in common.